Políticas públicas de emprego: a experiência alemã - Barbosa, Estela Capelas (2009)
The present work aims to investigate the importance of Labour Market Policies as a form of State interference in the Economy in Germany nowadays. For this purpose labour market economic theory is presented, in order to understand their positioning with regard to the actual activity performed by the government of such country. The Labour Market Policies themselves are described in detail to obtain its adjacent logic. Due to the perception that these theories are not sufficient to comprehend the logic of such activities, some historical, political, sociological and ideological factors from periods prior to the Reunification are presented. Therefore, the establishment of the Welfare State, in the post-war period, and its relevance to the edification of the institutional framework that provides the basis for the policies, are discussed. Furthermore, the influences of the German national formation, as well as the Weimar Republic and the emergence of Nazism, are analysed considering its impact over the government s behaviour on the policies matter. At last, some challenges brought about by the European Union are pointed out. The work concludes that the Labour Market Policies have primarily a social cohesion function in Germany, not necessarily producing pareto-efficient results